RELIGIOUS MODERATION: THE FOUNDATION OF INCLUSIVE ISLAMIC EDUCATION - Nasri, Ulyan; Muliadi, Erlan; Nuha, Ulin; Indinabila, Yunita; Gufran, M.; Aulia, Hesti Dina (Universitas Islam Negeri Mataram, 2024)
This research highlights the importance of religious moderation in the context of Islamic education to create an inclusive environment. Religious moderation plays a crucial role in shaping the foundation of Islamic education that provides space for all individuals regardless of belief differences. The aim of this research is to explore the practices and experiences of religious moderation in the context of Islamic education and its impact on inclusivity. The research methodology employed is a literature review, analyzing and synthesizing relevant literature from various sources. Data analysis involves collecting and reviewing literature on the practices of religious moderation in Islamic education and its impact on educational inclusivity. The findings indicate that the implementation of religious moderation in Islamic education can strengthen inclusivity and promote values of tolerance, dialogue, and mutual respect. The implications of this research underscore the importance of integrating values of religious moderation into Islamic educational curricula as a step to enrich educational experiences and reinforce inclusivity. Thus, this research provides a significant contribution to deepening understanding of how religious moderation can serve as a strong foundation for inclusive Islamic education.